In Vivo Pharmacodynamic Profile of Tigecycline against Phenotypically Diverse Escherichia coli and Klebsiella pneumoniae Isolates - Nicasio, Anthony M. (American Society for Microbiology (ASM), 2009)
Tigecycline is a glycylcycline with activity against Enterobacteriaceae, including multidrug-resistant isolates of Klebsiella pneumoniae and Escherichia coli producing extended-spectrum beta-lactamase (ESBL) and carbapenemases. Herein, we used an in vivo murine thigh model to characterize the pharmacodynamic profile of tigecycline against genotypically and phenotypically diverse K. pneumoniae and E. coli isolates. Doses of 3.125 to 300 mg/kg, divided 1 to 6 times daily, were administered subcutaneously against six (two nonresistant, one carbapenemase, and three ESBL producing) K. pneumoniae strains and five (two nonresistant and three ESBL producing) E. coli strains. The phenotypic profile (reported tigecycline MIC) for all isolates ranged from 0.125 to 2 μg/ml. Mean correlation coefficients of free (f) drug exposures (percentage of the dosing interval that free drug concentration remained above the MIC [fT>MIC], the ratio of the free drug area under the concentration-time curve/MIC [fAUC/MIC], and the ratio of maximum concentration of free drug in serum/MIC) for all 11 isolates were 0.595, 0.969, and 0.897, respectively. The fAUC/MIC was the pharmacodynamic parameter that best described the efficacy of tigecycline against both E. coli and K. pneumoniae. Interestingly, reductions in the number of CFU were noted even though doses achieved an fT>MIC of 0%. With respect to fAUC/MIC in the neutropenic model, the cumulative 80% and 50% effective pharmacodynamic indexes (EI(80) and EI(50)) for all 11 isolates were 8.4 and 4.7, respectively. An experiment in nonneutropenic mice infected with an ESBL-producing E. coli and K. pneumoniae isolate resulted in the lowest tigecycline fAUC/MIC EI(80) and EI(50) values at 1.8 and 1.0 for E. coli and 1.7 and 1.6 for K. pneumoniae. While the phenotypic profile of tigecycline appeared to drive efficacy irrespective of ESBL or carbapenemase production, the presence of a competent immune system markedly reduced this required exposure.